Born Globals’ Companies in The Context of Internationalization Strategy: A Bibliometric Analysis - Amina TANNAOUI; Karim GASSEMI (Communications of International Proceedings, 2025)
This study explores how research on Born Globals has evolved and identifies the main themes shaping this dynamic and growing field. While interest in firms that internationalize early has increased, the literature remains fragmented across journals and databases, making it difficult to trace key developments and gaps. This lack of synthesis has limited both theoretical progress and practical applications. To address this, the study applies a mixed-method approach, combining bibliometric analysis and a systematic literature review. A dataset of 217 peer-reviewed articles was extracted from Scopus and Web of Science. Using keyword co-occurrence, citation mapping, and network analysis, the study maps knowledge clusters, major trends and intellectual connections. Additionally, content analysis of highly cited articles within each cluster enhances the qualitative understanding of influential contributions. Findings reveal five thematic concentrations: Born Globals, internationalization, early internationalization, international business, and exporting. Within these clusters, key research emphases include innovation capabilities, international entrepreneurship, and the dynamics of the internationalization process. By bridging quantitative patterns and qualitative depth, this paper offers a comprehensive overview of Born Globals research. It not only clarifies the current state of knowledge but also highlights unresolved questions and suggests future research directions—particularly on performance outcomes and strategic behavior. Researchers and practitioners looking for a single, structured entry point into the Born Globals literature will find this study a valuable resource.
Keywords: Internationalization; Born Globals; Bibliometric Analysis; International New Ventures; Systematic Review